Assessment of genetic variability in mutant lines of greengram (Vigna radiata) using ISSR markers - SINGH, S K; G, SURESH B; LAVANYA, G R; ARYA, LALIT; BHAT, K V; HUSSAIN, Z; VERMA, M (The Indian Journal of Agricultural Sciences, 2014)
Out of 40 ISSR primers used in this study, 16 markers resulted in 163 amplifications with an average of 10.25 bands/ primer. Among 163 amplifications, 38 (42.89%) were found to be polymorphic. The genetic similarity coefficients among the mutant lines ranged from 0.88 to 0.99 with a mean value of 0.92. Cluster analysis based on ISSR profile grouped the genotypes into two major clusters which further divided into sub-clusters. The molecular diversity among the mutant lines was greater than that of the morphological diversity which also revealed that considerable amount of genetic variability has been generated through mutagenic treatment. The superiority of mutants AAIMM-10 and AAIMM-24 over the parental line in terms of yield and early maturity respectively proves the relevance of this study.